2022
DOI: 10.1073/pnas.2122161119
|View full text |Cite
|
Sign up to set email alerts
|

The C terminus of the mycobacterium ESX-1 secretion system substrate ESAT-6 is required for phagosomal membrane damage and virulence

Abstract: Significance Tuberculosis (TB), an ancient disease of humanity, continues to be a major cause of worldwide death. The causative agent of TB, Mycobacterium tuberculosis , and its close pathogenic relative Mycobacterium marinum , initially infect, evade, and exploit macrophages, a major host defense against invading pathogens. Within macrophages, mycobacteria reside within host membrane–bound compartments called phagosomes. Mycobacterium-indu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 73 publications
(127 reference statements)
1
33
0
Order By: Relevance
“…Mm M strain (ATCC #BAA-535) and Mtb H37Rv strain, mc 2 6206 ΔleuD ΔpanCD ( 60 ) expressing tdTomato, mWasabi, or EBFP2 were grown as previously described ( 59 , 61 ). For experiments to assay bacterial cording and number of macrophages in the trunk of the animal, zebrafish larvae were infected with 150-200 tdTomato-expressing Mm.…”
Section: Methodsmentioning
confidence: 99%
“…Mm M strain (ATCC #BAA-535) and Mtb H37Rv strain, mc 2 6206 ΔleuD ΔpanCD ( 60 ) expressing tdTomato, mWasabi, or EBFP2 were grown as previously described ( 59 , 61 ). For experiments to assay bacterial cording and number of macrophages in the trunk of the animal, zebrafish larvae were infected with 150-200 tdTomato-expressing Mm.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has pinpointed a specific role for ESAT-6 in phagosomal damage and virulence by identifying point mutations in ESAT-6 that allow substantial levels of secretion of ESAT-6 and other ESX-1 substrates yet cause loss of phagosomal membrane damage and/or virulence (Brodin et al, 2005; Osman et al, 2022; Zhang et al, 2016). To test the specific role of ESAT-6-induced phagosomal damage in mediating cell death in mTOR deficiency, we used esxA (ESAT-6) mutant Mm expressing either of two such ESAT-6 C-terminal point mutations, M83I and M93T (Brodin et al ., 2005; Osman et al ., 2022). Mm-ESAT-6 M83I and Mm-ESAT-6 M93T infections did not kill macrophages in mTOR-deficient zebrafish (Figure 6J).…”
Section: Resultsmentioning
confidence: 99%
“…ESX-1 increases macrophage death even in wild-type (mTOR competent) macrophages (Groschel et al ., 2016; Ramakrishnan, 2012) (Augenstreich et al ., 2017; Beckwith et al ., 2020; Behar et al, 2010; Davis and Ramakrishnan, 2009; Srinivasan et al, 2014), with ESAT-6-mediated phagosomal damage being a pre-requisite step (Bao et al ., 2021; Osman et al ., 2022; Simeone et al ., 2021; Srinivasan et al ., 2014; Zhang et al ., 2016). We show here that ESAT-6 induces phagosomal damage irrespective of whether the macrophage is mTOR-sufficient or -deficient.…”
Section: Discussionmentioning
confidence: 99%
“…While several ESX-1 genes were required for full Mmar virulence, the presence eccA1 seem to rather slows down Mmar proliferation within the flies. EccA1 is thought to regulate mycolic acid lipid synthesis (38), in addition to facilitate ESX-1-mediated secretion of the key mycobacterial virulence factors ESAT-6 and CFP-10 (39). Actually, Weerdenburg et al found that, on a cell culture level, EccA1 was required for virulence in mammalian but not in protozoan cells (24).…”
Section: Discussionmentioning
confidence: 99%